Characterization and bioactivity behavior of sol–gel derived bioactive vitroceramic from non-conventional precursors (2019)
ABSTRACT: The use of biomaterials has proven to be an excellent alternative in tissue regeneration due to the many possibilities they can offer. Bioactive glasses are a group of bioceramics that are being used in bone tissue engineering thanks to their biological properties, one of those being the bioactivity behavior. These bioactive glasses require a stabilization process by thermal treatments that partially crystallize the structure acquiring a vitroceramic state. In this study, sol–gel-derived bioactive vitroceramic was synthesized in a ternary system using non-conventional calcium and phosphate precursors in order to evaluate its bioactivity in the presence of simulated body fluid (SBF). The obtained bioactive vitroceramic was evaluated through XRD, FTIR, Raman and SEM to measure its chemical composition and morphology. The bioactivity test was carried out using cylindrical discs made with bioactive vitroceramic; those discs were analyzed in 7 and 14 days of exposition. The formed layer was studied with XRD, FTIR, SEM and EDX analysis. The results have shown that synthesized bioactive vitroceramic has similar composition and crystallinity of those reported in the same system indicating the appropriate use of different precursors. Likewise, the bioactivity behavior showed the formation of a non-crystalline hydroxyapatite layer on bioactive vitroceramic surface with a Ca/P ratio similar to that in bone, which means that the synthesized material can be used in bone tissue engineering